THE ARTISTIC EXPRESSION OF THE HARMONY BETWEEN HUMAN AND NATURE IN THE WORKS OF NORMUROD NORQOBILOV (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
This article examines the artistic features of Normurod Norqobilov’s prose, focusing on the complex relationship between human psychology and natural phenomena. Using the novella “The Wolf that Roamed the Village” as an example, the study explores themes of human values, loyalty, devotion, and ecological education conveyed through symbolic animal imagery. The author harmoniously integrates the depiction of inner experiences with natural landscapes, highlighting the aesthetic qualities of contemporary Uzbek literature.